Karabük Ovacık Çukur Camisi Yapı Malzemelerinin Arkeometrik Analizleri - Eroğlu, Murat; Bi̇lgen, Muhammet; Yeti̇ş, Ezgin; Kadioğlu, Yusuf Kağan; Deni̇z, Kıymet (Istanbul University, 2021)
This study aims to determine the conservation status of Karabuk Ovacik Cukur Mosque building materials using analytical methods. Cukur Mosque is connected to the Ovacik district of Karabuk and is 12 km away from the district center. The distance between Karabuk and Ovacik is 48 km. Originally, the wooden roofed building consisted of a harim. Stone, mortar, rendering, and paint samples of the mosque were examined due to their architectural properties, dated to the end of the 19th and beginning of the 20th century. Analytical methods were used to determine the physical, chemical, and petrographic properties of building materials, including raw material samples. The following techniques were used for performing the analysis: Silicate aggregate/binder analysis, granulometric sieve analysis-particle size distribution, X-Ray Fluorescence analysis, Confocal Raman Spectroscopy analysis, Fourier Transform Infrared Spectroscopy analysis, and petrographic examinations. Material samples were photographed, documented, and coded for laboratory studies within the scope of the study. The results showed the identification of aggregate binder properties in mortars and renderings and cement in some samples. Conversely, various pigments of mineral origin and organic properties were identified in paints.
Keywords: Çukur Camisi; Yapı malzemeleri; Arkeometri; Pigment; Bağlayıcı; Petrografi; XRF; KRS; FT-IR; Çukur Mosque; Historical Construction Materials; Archeometry; Pigment; Binders; Petrography; XRF; CRS; FT-IR; 11. Sustainability